Interlocking passive brick set: the design of interlocking building components with connecting air cavities for heat dissipation and as a complement to the Heating, Ventilation, and Air Conditioning (HVAC) system - Kongphat Phaiboonnukulkij (Budownictwo i Architektura)
This dissertation explores the design and implementation of the "Interlocking Passive Brick Set," a building component aimed at enhancing thermal efficiency and optimising the performance of Heating, Ventilation, and Air Conditioning (HVAC) systems. The bricks demonstrate thermal resistance and low thermal transmittance, reflecting their ability to manage heat flow and dissipation effectively. The research focuses on the interaction between the exterior and interior surfaces of the brick set, where the exterior is exposed to a hot environment, and the interior remains cooler. The design incorporates a central air cavity with lower thermal transmittance than solid surfaces. This cavity facilitates a heat dissipation cycle: hotter air rises and is expelled through the top compartment, while cooler air descends, cooling the space. This convective process enhances the overall thermal regulation within the structure. The data explain the discrepancy between predicted and measured thermal performance in interlocking brick systems and how the integrated air cavity addresses these issues. Heat-flux measurements were correlated in a general form to enable designers to account for convection at both the interior and exterior surfaces.